An interventional exploratory study to assess the effect of footwear on postural stability and strategy during quiet standing. Issue 1 (1st January 2021) - Hausselle, J.; Haddox, A. G.; Kasitz, J.; Azoug, A.
ABSTRACT: A stable quiet stance is achieved by controlling the relative position of the center of pressure and the vertical projection of the center of mass. The best postural performances include efficient strategies to mitigate external perturbations. Footwear impacts postural stability and strategy by affecting cutaneous proprioception and ankle proprioception in the case of heeled shoes. The purpose of this study was to quantify the effects of four common footwear conditions, i.e . barefoot, sports, flats, and heels, on postural stability and strategy during quiet standing of healthy young women. Postural stability and strategy were assessed overall and in the antero-posterior and medio-lateral directions using five parameters: total sway, average center of pressure (COP) velocity, α value computed using detrended fluctuation analysis, hip over ankle ranges of motion, and power of the COP time series. Significant differences with barefoot were consistently found when wearing heels, namely a decrease in postural sway and average COP velocity. Results seemed counter-intuitive as they indicate an apparent increase in postural stability when wearing heels. A deeper analysis revealed a more complex scheme. A potential tightening of the motion when wearing heels, combined with an increase of the neutral plantarflexion angle, shifts the postural strategy towards a predominant hip strategy. Finally, proprioception did not play a key role. This study highlighted the complexity of the multifactorial interactions between footwear characteristics and postural strategies. Additional work is needed to develop footwear that will enhance postural stability of populations at risk, such as pregnant women or the elderly.